The Influence of eWOM and Brand Image on Consumer Buying Interest in Azarine Products - Anisa Fanestya Nofalia; Albari Albari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to provide new information about the influence of Electronic Word of Mouth (eWOM) on consumer decisions, especially on Azarine beauty products. The focus of this research analyze the extent to which the quantity and credibility of eWOM affect brand image and consumer purchase intention. To answer these objectives, the author used quantitative methods through an online survey involving 210 respondents. Data were analyzed using the Structural Equation Modeling (SEM) technique based on Partial Least Square (PLS) with the help of SmartPLS software. The results showed that eWOM quantity has a significant effect on eWOM credibility, brand image, and purchase intention. In addition, eWOM credibility is proven to have a positive impact on brand image and purchase intention. Brand image also acts as a strong mediating variable in shaping consumer purchase intention. The findings suggest that companies need to manage eWOM strategies more purposefully, especially by increasing the credibility of messages conveyed by consumers.